Cryofibrinogen-associated glomerulonephritis diagnosed by mass spectrometry and immunoelectron microscopy - Masanori Sudo; Yuichi Sakamaki; Michihiro Hosojima; Suguru Yamamoto; Yumi Ito; Naofumi Imai; Yoshikatsu Kaneko; Shin Goto; Chih-Ping Li; Akira Shimizu; Ichiei Narita (Elsevier, 2019)
A 60-year-old male presented with accelerated hypertension, renal insufficiency, proteinuria, and hematuria. Percutaneous kidney biopsy revealed membranoproliferative glomerulonephritis (MPGN) without any immunoglobulin and complement deposition. On performing electron microscopy, deposits with a tubular, organized structure and approximately 60 nm in diameter were detected in the glomerular subendothelial spaces and mesangial areas. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) demonstrated the significantly increased deposition of fibrinogen and fibronectin in glomeruli. Immunohistochemistry and immunoelectron microscopy demonstrated that the deposits were composed of fibrinogen. Here we report a case of cryofibrinogen -associated GN in which LC-MS/MS and immunoelectron microscopy were useful for diagnosis. When MPGN with organized deposits without the deposition of immunoglobulins and complements is diagnosed, we considered the cryofibrinogen-associated GN in one of the differential diagnosis, and even skin symptoms cannot be detected. Keywords: Cryofibrinogen-related kidney disease, Liquid chromatography-tandem mass spectrometry, Immunoelectron microscopy